Improving Free Poetry Writing Skills Using the Cooperative Roud Table Type Model in Elementary Schools - Lulu Kamila Zahra; Rusdial Marta; Yolanda Pahrul (Universitas Muhammadiyah Enrekang, 2022)
This research is motivated by the low ability of students to choose, arrange words, and express ideas in writing, especially writing poetry. One solution to overcome this problem is to use a round table cooperative learning model . The purpose of this study was to describe the planning, implementation and improvement of free poetry writing skills using the round table cooperative model in elementary schools. This research method is a classroom action research carried out in two cycles. Each cycle consists of two meetings and four stages, planning, action, observation and reflection. The subjects of this study were 14 grade IV students, 7 boys and 7 girls. Data collection techniques in the form of observation, documentation and tests. The results of this study can be concluded that the pre-cycle obtained an average class value of 57.4 with classical completeness of 42.85%, increased in cycle 1 meeting 1 to 59.28 with classical completeness of 50%, increased in cycle 1 meeting 2 to 67.5 with a classical completeness of 64.28%. The class average score in cycle 2 meeting 1 was 71.78 with classical completeness of 71.42% and increased in cycle 2 meeting 2 which was 77.14 with classical completeness of 85.71%. Thus it can be concluded that by using the round table type of cooperative learning model can improve the skills of free poetry writing class IV SDN 004 Bangkinang Kota. Keywords: Cooperative round table type, Writing, and Free Poetry